The capture of Integral Education by neoliberal perspectives in local contexts: the case of the Municipal Education Network of Florianópolis (Práxis Educativa, 2026)
This article critically analyzes how the concept of Integral Education has been interpreted and translated within the Municipal Education Network of Florianópolis, Santa Catarina, Brazil, by comparing national legal frameworks (Federal Law no. 14,640/2023 and Ordinances of the Ministry of Education – MEC no. 1,495/2023 and no. 2,036/2023) with local regulatory documents (Ordinance of the Municipal Department of Education of Florianópolis – SMEF no. 222/2025, Floripa Tempo Integral and Escola em Tempo Integral, Official Letter GS/SME/PMF no. 166/2025, and Official Letter DEF/SME no. 11/2025). This is a qualitative and exploratory study based on documentary analysis guided by the Policy Cycle Approach and Policy Enactment framework, aiming to identify processes of policy recontextualization in Full-Time Integral Education. The findings show that, while national policy prioritizes holistic human development, democratic governance, and an integrated curriculum, municipal policy reveals curricular narrowing, centralized decision-making, and an emphasis on measurable performance, associated with managerialist rationalities. It is concluded that local recontextualization leads to the capture of the emancipatory meaning of Integral Education, limiting its transformative potential and potentially exacerbating educational inequalities, thus indicating the need to revise the policy based on democratic participation and curricular justice.Keywords: Integral education. Education policies. Neoliberalism.